20.2k views
0 votes
Solve the system by substitution 3x+y=-16 and y=-x-4

User Artoonie
by
4.6k points

1 Answer

3 votes

Answer:

x = - 6

y = 2

Explanation:

Equations

3x+y=-16

y=-x-4

Solution

Put y in the second equation into the first equation

3x - x - 4 = - 16

2x - 4 = - 16

2x = - 16 + 4

2x = -12

2x/2 = -12/2

x = - 6

y = -x - 4

y = - -6 - 4

y = 6 - 4

y = 2

===========================

3x + y = - 16

3x + 2 = - 16

3x = -16 - 2

3x = - 18

3x/3 = -18/3

x = -6

User WKordos
by
4.9k points